De inquieto a ateu: ecos de Locke na Enciclopédia - Santos, Antônio Carlos dos (Discurso, 2021)
The purpose of this article is to think of the image of the atheist in the entries "Atheist" and "Atheism" of the Encyclopaedia and to trace the possibility of understanding the marks of Lockian thought. These traits are fundamental for understanding the way in which there was a change in the image of the atheist between the 17th century in England and the 18th century in France and how this change will positively contribute to a better acceptance of the non-believer in the center of modern society. To provide greater completeness to the text, it is divided into two parts: in the first, we will investigate the profile of the authors of the entries “Atheist” and “Atheism”; in the second, we will properly examine the two entries in the Encyclopedia and seek to detect the echoes of Locke's political thought.